Nigeria-Swedish Economic Relations and Impactful Benefits for Delta State - C. Nwokolobia, Anthony; C. Okolie, Ugo (Malikussaleh Social and Political Reviews, 2025)
Nigeria and Sweden maintain a dynamic and evolving economic partnership, marked by trade, investment, and technological collaboration. This study explored Nigeria-Sweden economic relations and assessed their significant benefits for Delta State, a resource-rich area in the Niger Delta. The study was anchored on dependency theory to explain how economic ties influence local development and help address structural inequalities. Swedish investments, particularly in renewable energy and technology, present transformative opportunities for driving industrial diversification and job creation in Delta State. However, challenges such as bureaucratic hurdles, political instability, and security issues hinder the full realization of these economic benefits. The study concluded that strengthening Nigeria-Sweden economic collaboration could serve as a catalyst for sustainable development in Delta State and support Nigeria’s broader economic diversification efforts. To enhance its impact, the study recommended, among others, that Nigeria, particularly Delta State, should strive to negotiate more favorable and inclusive trade agreements with Sweden that benefit both parties. These agreements should focus on lowering trade barriers, enhancing market access, and ensuring a fair exchange.